1984
DOI: 10.1111/j.1471-4159.1984.tb06689.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monensin and Colchicine on Myelin Galactolipids

Abstract: Monensin and colchicine have been used in a variety of systems to disrupt functioning of the Golgi apparatus and transport of Golgi-derived vesicles to the plasma membrane. In this study the effects of monensin and colchicine on the synthesis of cerebroside and sulfatide and their appearance in myelin were examined to determine whether these myelin components are processed through the Golgi apparatus. Brain slices from rats 17 days old were incubated with [3H]galactose and [35S]-sulfate to label cerebroside an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

1984
1984
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 25 publications
1
21
1
Order By: Relevance
“…Evidence exists suggesting that cerebroside sulfates and PLP are delivered to the myelin membrane through similar mechanisms. The transport of either of these components is disrupted by monensin (Townsend and Benjamins, 1983;Townsend et al, 1982Townsend et al, , 1984Sat0 et al, 1986) and by colchicine (Bizzozero et al, 1982b;Townsend et al, 1982Townsend et al, , 1984. Furthermore, recent studies from our laboratories strongly suggested the possibility of an associated or coupled transport of both components.…”
Section: Discussionmentioning
confidence: 88%
“…Evidence exists suggesting that cerebroside sulfates and PLP are delivered to the myelin membrane through similar mechanisms. The transport of either of these components is disrupted by monensin (Townsend and Benjamins, 1983;Townsend et al, 1982Townsend et al, , 1984Sat0 et al, 1986) and by colchicine (Bizzozero et al, 1982b;Townsend et al, 1982Townsend et al, , 1984. Furthermore, recent studies from our laboratories strongly suggested the possibility of an associated or coupled transport of both components.…”
Section: Discussionmentioning
confidence: 88%
“…Brain slice preparations have been used previously to study myelin protein processing and the incorporation of fatty acids and phospholipids into myelin (Benjamins et al, 1978;Townsend et al, 1984;Townsend et al, 1982;Miller et al, 1977). In this report, the use of brain slices has been extended to measure the turnover rates of myelin mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…GalCer is synthesized by the enzyme ceramide galactosyl transferase (CGT) in the endoplasmic reticulum (Stahl et al, 1994;Schaeren-Wiemers et al, 1995b), and because sulfation of GalCer occurs in the Golgi (Benjamins et al, 1982;Tennekoon et al, 1983;Farrer et al, 1995), GalCer has to pass through the Golgi for synthesis of sulfatide (Van der Bijl et al, 1996). Finally, sulfatide (Townsend et al, 1984) and presumably also GalCer are transported via vesicular transport to the myelin membrane. A mechanism proposed for the sorting and trafficking of proteins and lipids in polarized epithelial cells involves an association of membrane proteins with glycolipid-enriched microdomains in the trans-Golgi network (TGN) and the subsequent budding and transport via carrier vesicles to specific plasma membrane domains (Simons and Wand-inger-Ness, 1990).…”
Section: Introductionmentioning
confidence: 99%